2019
DOI: 10.3389/fendo.2019.00643
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Receptor Polymorphisms With Activity of Acromegaly, Vitamin D Status and Risk of Osteoporotic Fractures in Acromegaly Patients

Abstract: Introduction: The vitamin D receptor (VDR) gene is one of the most widely studied tumorigenesis-related genes. The primary objective of this study was assessment of possible roles of VDR gene polymorphisms in acromegaly, with regard to the activity of the disease and compared them with a control group. Furthermore, we have assessed the associations between these polymorphisms with vitamin D status as well as with TBS (trabecular bone score) and risk for osteoporotic fracture in acromegaly patients.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In the present study, we found that TBS values were lower in acromegalic patients compared to age, BMI, and sex-matched healthy controls, while no significant differences were observed in BMD values between the two groups, both at lumbar and femoral sites. These data are in line with the results reported by other authors, although some studies did not find significant differences in TBS values between patients and matched controls [ 23 , 41 , 42 , 43 , 45 , 46 , 47 ]. Furthermore, we observed that both BMD and TBS values were significantly lower in hypogonadal patients compared to the eugonadal ones, thus confirming the pivotal role of gonadal status on both bone density and quality in acromegaly [ 6 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we found that TBS values were lower in acromegalic patients compared to age, BMI, and sex-matched healthy controls, while no significant differences were observed in BMD values between the two groups, both at lumbar and femoral sites. These data are in line with the results reported by other authors, although some studies did not find significant differences in TBS values between patients and matched controls [ 23 , 41 , 42 , 43 , 45 , 46 , 47 ]. Furthermore, we observed that both BMD and TBS values were significantly lower in hypogonadal patients compared to the eugonadal ones, thus confirming the pivotal role of gonadal status on both bone density and quality in acromegaly [ 6 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Currently, few studies have analyzed TBS in patients with acromegaly [ 23 , 24 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In most cases, the authors reported lower TBS values in acromegalic patients compared to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we do not have other useful tools to detect bone damage and estimate real risk for fractures. As we showed in a previous study, usage of FRAX could be functional in combination with other tools such as TBS [27]. The early diagnosis of acromegaly and investigations for new markers as well as for new diagnostic methods for assessing the risk of osteoporotic fractures are very important to improve care of acromegaly patients.…”
Section: Discussionmentioning
confidence: 89%
“…Assessment of bone quality can improve this evaluation. Recently introduced trabecular bone score (TBS) method is a promising tool, which enables to assess bone tissue microarchitecture ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%